Cura, salute, vita, morte: diritto dei principi o disciplina legislativa? (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The Italian Parliament is currently debating about a legislative bill on informed consent and advance decisions. The draft comes after years of public debates, judicial decisions and failed legislative proposals. The Author points out the qualities and deficiencies of the bill, underlining the importance of a fair parliamentary debate in order to avoid dangerous manipulations of a law which has to be based on solid principles and on the respect for fundamental rights.
Keywords: Informed consent; Draft law; End of life decisions; Advance decisions; Italian Parliament